Parametrizing GP Trees for Better Symbolic Regression Performance through Gradient Descent [Poster] - Pietropolli, Gloria (2023)
Pietropolli, G., Camerota verdù, F. J., Manzoni, L., & Castelli, M. (2023). Parametrizing GP Trees for Better Symbolic Regression Performance through Gradient Descent [Poster]. In S. Silva, & L. Paquete (Eds.), GECCO '23 Companion: Proceedings of the Companion Conference on Genetic and Evolutionary ComputationJuly 2023 (pp. 619-622). Association for Computing Machinery (ACM). https://doi.org/10.1145/3583133.3590574